The influence of excessive alcohol consumption on the course and development of dermatoses - A. F. Gatina; N. P. Teplyuk (Лечащий Врач, 2022)
The spectrum of dermatoses associated with alcohol dependence syndrome is quite extensive. Ethanol and other components of alcoholic beverages affect the structure of the skin and blood vessels, impair immune function, increase the risk of exacerbation of existing skin diseases, and also make the skin vulnerable to infectious diseases. The review analyses the toxic effect of ethanol, in particular its effect on the appearance and progression of skin diseases For this purpose, the review provides the results of both foreign and domestic clinical studies on the development and exacerbation of dermatoses due to excessive consumption of alcoholic beverages. It is noted that the addiction of patients to alcohol may be considered as one of the main causes of the most common skin diseases and pathological conditions with skin manifestations. The vastness of the spectrum of such diseases is emphasized and the following diseases – rosacea, malignant neoplasms, porphyria, psoriasis, urticaria, sporotrichosis are considered in detail. In addition, the article provides a brief description of the effects of ethanol on the human body, in particular, on the skin, blood vessels and the immune system, and also establishes the mechanisms of its action on the severity of the course of the listed dermatological diseases or pathologies with skin manifestations. The data are given that with specific skin pathologies, excessive alcohol consumption leads to a worsening of the reaction to the treatment. For some diseases, it is also noted how the type of alcoholic beverage affects the condition of the patient's skin. At the same time, the process of alcohol metabolism is considered in detail, as a result of which the function of the skin barrier is disrupted. The conclusion is made as to how awareness of dermatoses and their connection with alcohol abuse can affect the detection of the disease in the early stages and its therapy, as well as the treatment of alcohol dependence. At the same time, it is emphasized that the data of modern scientific research on the chosen topic is insufficient, which makes it relevant for further and more detailed study.